The impact of innovation on the economy - Kurova A. A. (Science and education: future development, 2019)
in this paper, the interaction of innovation and Economics is considered. The latest technological changes and the consequences of innovative changes reflected in the economy are presented.
Keywords: инновация; технологии; глобализация; общество; экономическое развитие; Society; innovation; technology; globalization; economic development